Post-match Recovery Practices in Professional Football: Design, Validity, and Reliability of a New Questionnaire - Querido, Sérgio M.; Brito, João; Figueiredo, Pedro; Carnide, Filomena; Vaz, João R.; Freitas, Sandro R. (Frontiers in Sports and Active Living, 2021)
Introduction: Although several approaches have been proposed to mitigate the post-match fatigue, few studies have been conducted in team sports to understand which types of recovery methods are used and the underlying reasons for the medical and technical staff choices. This study aimed to develop a valid and reliable online questionnaire to assess recovery practices implemented by football clubs within 72 hours post-match. Methods: Two research members developed the original questionnaire proposal, and two experts in sports science and sports medicine confirmed the content and face validities. Then, 20 football coaches (age: 39.4±6.8 yrs) with a minimum of 5 years of experience in professional football (9.1±4.9 yrs) and academic background participated in the questionnaire ecological validity and reliability. Questionnaire acceptability and relevance were determined using descriptive statistics. Results: After confirming the content and face validity, one questionnaire section with 2 questions was excluded due to lack of relevance, 7 open-ended questions were removed due to small participants’ adherence (i.e. 45.4%), and one section was divided into three to facilitate reading clearance. The remaining sections were considered acceptable and relevant (>94.1%). 91.8% of nominal and ordinal items derived from the questionnaire questions showed good to very good reliability outcomes (average k classification: 0.73±0.13; min-max: 0.22-1.00, p<0.05; average wk classification: 0.82±0.15; min-max: 0.22-1.00, p<0.05). Conclusions: This work provided a novel, valid, reliable, and easy-to-use tool to examine the post-match recovery practices in elite football contexts.